2014
DOI: 10.3945/jn.114.192989
|View full text |Cite|
|
Sign up to set email alerts
|

Phytic Acid Concentration Influences Iron Bioavailability from Biofortified Beans in Rwandese Women with Low Iron Status

Abstract: PA strongly decreases iron bioavailability from iron-biofortified beans, and a high PA concentration is an important impediment to the optimal effectiveness of bean iron biofortification. Plant breeders should focus on lowering the PA concentration of high-iron beans. This trial was registered at clinicaltrials.gov as NCT01521273.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 48 publications
(71 reference statements)
5
99
0
1
Order By: Relevance
“…Resolving anaemia has proven to be difficult, despite interventions such as iron and folic acid supplementation of adult women, iron fortification of grain flours, multi-micronutrient fortification of commercial foods or supplementation via powders (UNICEF 2006). Biofortification (conventional cross-breeding and/or genetic modification for high iron traits) of crops such as beans, cassava, wheat and pearl millet is increasingly promoted as a food-based approach to addressing anemia through the diet (Petry et al 2014). However, even with all kinds of interventions combined, a halving of the global rate of iron deficiency anaemia by 2025 would require an ARR of 5.3 %.…”
Section: Global Problems and Global Goalsmentioning
confidence: 99%
“…Resolving anaemia has proven to be difficult, despite interventions such as iron and folic acid supplementation of adult women, iron fortification of grain flours, multi-micronutrient fortification of commercial foods or supplementation via powders (UNICEF 2006). Biofortification (conventional cross-breeding and/or genetic modification for high iron traits) of crops such as beans, cassava, wheat and pearl millet is increasingly promoted as a food-based approach to addressing anemia through the diet (Petry et al 2014). However, even with all kinds of interventions combined, a halving of the global rate of iron deficiency anaemia by 2025 would require an ARR of 5.3 %.…”
Section: Global Problems and Global Goalsmentioning
confidence: 99%
“…Based on human studies, the original estimate of 5 percent bioavailability has been increased to 7 percent. A bioavailability study of young women found that the participants absorbed significantly greater amounts of iron from biofortified beans compared to the conventional beans [13].…”
Section: Setting Iron Target Levels For Bean Breeders and Establishinmentioning
confidence: 99%
“…At normal PA concentrations, fractional iron absorption from the biofortified beans (7.1%) was lower than for the control beans (9.2%), and the total amount of iron absorbed from the iron-biofortified beans was only slightly higher (19%) compared to the control beans. However, dephytinization increased fractional iron absorption and, after 95% dephytinization, iron absorption from both beans increased to about 13% and the total amount of iron absorbed from the biofortified bean was 51% higher than from control beans.A potential explanation for the results from Petry et al [4] is that some of the additional iron bred into the beans is stored as a non-bioavailable form of iron bound to PA. This is consistent with findings from Hoppler et al in their study examining iron speciation in beans [7].…”
mentioning
confidence: 99%
“…The biofortified beans were provided as part of a composite meal using a multiple meal design, which has been shown to better reflect real-life iron bioavailability [2]. In the multiple meal studies, iron bioavailability from biofortified beans consumed with potatoes or rice was modest, ranging from 3.8% to 7.3% [3,4,5]. However, in these studies, the total amount of iron absorbed from biofortified beans in these studies per woman per day ranged from 234 to 431 ”g, and represented up to 30% of the physiologic requirement for non-pregnant non-lactating women of reproductive age [6].…”
mentioning
confidence: 99%